SISTEM IRIGASI CERDAS UNTUK PERTANIAN PERKOTAAN DI DEPOK: MEMBERDAYAKAN KELOMPOK TANI DRANGRANG - Kurniasih, Ratih; Sugeru, Herik; Nurthoyibah, Hilmi Aini; Abadi, Kalingga Kencana; Musa, Purnawarman (Universitas katolik Musi Charitas, 2025)
Purpose: Urban agriculture often faces challenges in efficient water management due to limited resources, climate change, and the limited availability of time among farmers who are actively working in metropolitan areas such as Jakarta. This condition necessitates the adoption of technologies that support efficiency and automation in water management. This community service program aims to improve water use efficiency through the development and training of smart irrigation technology based on soil moisture and weather sensors. Methodology: The program was implemented at the D'rangrang Farmers Group through a Community Partnership Empowerment scheme funded by the Directorate of Research Technology and Community Service. The methodology included technology socialization, installation training, system utilization monitoring, and evaluation of implementation outcomes. Findings: The results indicate that the application of smart irrigation technology reduced water consumption by up to 30 percent compared to conventional irrigation methods. In addition, farmers demonstrated increased awareness of the importance of precise and efficient water management in urban agriculture. Practical Implications: The implementation of smart irrigation supports improved productivity and sustainability of urban farming practices. The technology enables farmers to manage water resources more efficiently despite time constraints associated with urban employment. Originality Value: This program integrates sensor based irrigation technology with community empowerment through practical training. The approach offers a replicable model for enhancing sustainable urban agriculture in other regions.